2017
DOI: 10.1093/treephys/tpx087
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of light quality on leaf gas exchange and hydraulic properties of silver birch (Betula pendula)

Abstract: Leaves have to acclimatize to heterogeneous radiation fields inside forest canopies in order to efficiently exploit diverse light conditions. Short-term effects of light quality on photosynthetic gas exchange, leaf water use and hydraulic traits were studied on Betula pendula Roth shoots cut from upper and lower thirds of the canopy of 39- to 35-year-old trees growing in natural forest stand, and illuminated with white, red or blue light in the laboratory. Photosynthetic machinery of the leaves developed in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Under environmental stresses, the photosynthetic ability is usually affected by stomatal behavior in higher plants. Many studies indicated that abiotic stresses resulted in a decline in P n , T r , and G s , and an increase in C i [ 31 , 32 , 33 ]. Here, highland barley showed high P n , T r , G s , and C i relative to the other three plants, indicating that gas exchange was more effective in highland barley under high light exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Under environmental stresses, the photosynthetic ability is usually affected by stomatal behavior in higher plants. Many studies indicated that abiotic stresses resulted in a decline in P n , T r , and G s , and an increase in C i [ 31 , 32 , 33 ]. Here, highland barley showed high P n , T r , G s , and C i relative to the other three plants, indicating that gas exchange was more effective in highland barley under high light exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus possible that the higher relative presence of BL in the morning is responsible for the rapid K leaf , enhancement during the transition from dark to light (Voicu et al ., 2008; Ben Baaziz et al ., 2012; Grunwald et al ., 2022). Additionally, during daytime, BL was found to induce a greater increase in K leaf in shaded leaves (normally exposed to little or no BL), as compared with leaves directly irradiated by the sun (Niglas et al ., 2017). This may be an adaptation for efficient hydraulic adjustment to compliment the increased stomatal and photosynthetic activity stimulated by the fast‐changing patterns of sunflecks, which increases the BL proportions shaded leaves momentarily receive (Niglas et al ., 2017).…”
Section: How Light Quality Affects Kleafmentioning
confidence: 99%
“…Additionally, during daytime, BL was found to induce a greater increase in K leaf in shaded leaves (normally exposed to little or no BL), as compared with leaves directly irradiated by the sun (Niglas et al ., 2017). This may be an adaptation for efficient hydraulic adjustment to compliment the increased stomatal and photosynthetic activity stimulated by the fast‐changing patterns of sunflecks, which increases the BL proportions shaded leaves momentarily receive (Niglas et al ., 2017). Since xylem conduits consist of dead tissue, the rapid and dynamic response of K leaf to light quality and intensity, which occurs within minutes, necessitates the involvement of physiological regulatory mechanisms.…”
Section: How Light Quality Affects Kleafmentioning
confidence: 99%
See 1 more Smart Citation
“…To maximize their morphological growth and physiological processes, plants must be able to sense and respond to changes in light properties, which vary spatially and temporally in natural conditions, especially within forest canopies. There is a marked decrease in light intensity from the upper to the lower canopy, with upper-canopy foliage exposed to higher irradiance than lower-canopy foliage shaded by leaves and branches residing in the upper canopy [24][25][26][27][28]. There is a need to clarify how iWUE varies with light intensity.…”
Section: Introductionmentioning
confidence: 99%